Leading and Managing Safe Secondary Schools in Gauteng - Morris, Renald (My University, 2018)
School-based violence in South Africa has reached unacceptably high levels in most public schools; to the extent that it has become a barrier to education. Despite various combined and individual efforts by government, civil society groups and practitioners over the past two decades, the situation shows no sign of abating. As a result, schools are finding it harder to deliver on education outcomes and this, in turn, leads to a situation where government can be seen to be failing in its constitutional mandate to provide physical infrastructure (schools, teachers and teaching materials) and to ensure teaching and learning happens in a safe and secure environment. The purpose of this research study was to create a better understanding of safe schools and school safety, and to identify and present leadership strategies that were found to contribute to creating safe teaching and learning environments. This was accomplished using a qualitative research approach. The results of the study prove that in the context of South Africa, a social justice approach to school safety is necessary and relevant because it provides an all-encompassing view of factors that impact on school safety. A general finding that emerged from the study further shows that there is a significant difference between the definition of “school safety” provided by the majority of School Governing Bodies (SGBs) and the definition provided by the majority of principals. SGBs defined school safety quite narrowly, focusing mainly on technical aspects of school safety, while principals took more of a broad social justice approach, which included both technical and psychological aspects of school safety. The study concluded that these differences point to one of the reasons why school violence persists and why principals find it hard to lead and manage safe schools.
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy October, 2018.
Keywords: Educational leadership; School management and organization--South Africa